Toward a Holistic Understanding of Sustainability in Corporations: Resource-Based View of Sustainable Supply Chain Management - Arda, Ozlem Ayaz; Montabon, Frank; Tatoglu, Ekrem; Golgeci, Ismail; Zaim, Selim (Emerald Group Publishing Ltd, 2021)
Purpose While the three interconnected aspects of the triple bottom line -environmental, social and economic sustainability- are well-established, these aspects have insufficiently been addressed together in the supply chain management literature. Thus, the purpose of this paper is to examine whether environmental and social performance mediates the relationship between environmental management practices and operational performance and whether operational performance mediates the relationship between environmental and social performance and financial performance. Design/methodology/approach Drawing on a data set of 208 firms operating in a wide range of manufacturing industries, the authors test the hypotheses using structural equation modeling. The research context for the study is Turkey, an important emerging market and one of the nexuses of European and Asian supply chains. Findings The findings indicate that all three aspects of sustainability have mutually supportive relationships as demonstrated by positive mediating mechanisms between environmental management practices and operational performance and between environmental and social performance and financial performance. The mediation results correspond with the resource-based view. They indicate that building up capabilities and resources in the form of environmental management practices supports three areas of the triple bottom line and boosts firms' financial performance. Originality/value Research on sustainability is well-established, yet supply chain management research has, thus, far paid insufficient attention to all three aspects. This paper, thus, sets itself apart by explicitly considering all three aspects of sustainability and contributes to understanding how they relate to one another.
Keywords: Sustainability; Environmental performance; Financial performance; Social performance; Sustainable manufacturing; MEASURING ORGANIZATIONAL PERFORMANCE; ENVIRONMENTAL-MANAGEMENT; FINANCIAL PERFORMANCE; SOCIAL PERFORMANCE; COMPETITIVE ADVANTAGE; BUSINESS PERFORMANCE; QUALITY MANAGEMENT; STRATEGY RESEARCH; GREEN; FIRM